Nanobiomaterials Used in Cancer Therapy: An Up-To-Date Overview - Iulia Ioana Lungu; Alexandru Mihai Grumezescu; Adrian Volceanov; Ecaterina Andronescu (Molecules, 2019)
The disadvantages that come with traditional cancer treatments, such as chemotherapy and radiotherapy, generated a research shift toward nanotechnology. However, even with the important advancements regarding cancer therapy, there are still serious stepping stones that need to be addressed. The use of both nanotechnology and nanomedicine has generated significant improvements in nano-sized materials development and their use as therapeutic, diagnosis, and imaging agents. The biological barriers that come from the healthy body, as well from the tumorous sites, are important parameters that need to be taken into consideration when designing drug delivery systems. There are several aspects of extreme importance such as the tumor microenvironment and vasculature, the reticuloendothelial system, the blood−brain barrier, the blood−tumor barrier, and the renal system. In order to achieve an effective system for cancer therapy, several characteristics of the nanoparticles have been outlined. Moreover, this review has also focused on the different types of nanoparticles that have been studied over the years as potential candidates for cancer therapy.